Study and evaluation of abrasive water jet turning process performance on AA5083 - Kartal, F. (Wiley, 2020)
AbstractIn this study, the effect of processing parameters on surface roughness and macro surface characteristics was analyzed during the machining of Ø30 mm and 300 mm aluminum alloy AA5083 abrasive water jets. As the processing parameters (up to 10 mm min−1, 15 mm min−1, 20 mm min−1 and 25 mm min−1), abrasive flow rate (50 g min−1, 150 g min−1, 250 g min−1 and 350 g min−1), the lathe chuck rotational speed (25 min−1, 50 min−1, 75 min−1 and 100 min−1) and the nozzle approach distance (2 mm, 5 mm, 8 mm and 11 mm) were used in experiments. In experimental studies, the pump pressure (360 MPa) was used as a constant, in the form of an abrasive Garnet (100 mesh), and the nozzle diameter as 0.76 mm. According to the findings, the best results in terms of surface roughness were obtained as a result of turning speed and abrasive flow rate. When the macro surface characteristics were examined, it was found that the lathe chuck rotational speed increased, the rate of nozzle progression was low, the rate of abrasive flow was high and the nozzle approach distance was lower and the smoother surfaces were obtained.